Nutritive Values and Farmers Preference of Barley (Hordeum Vulgare L.) Varieties for Food Feed Traits - Hailemichael, Shewangizaw (Debre Berhan University, 2024)
The aim of this study was to determine and investigate the food-feed relationship, nutritional values, and farmer choice with regard to particular barley varieties straw used as animal feed in Ethiopia's central highlands. The experiment was conducted at Gudo Beret Kebele in the Basona Worena District, North Shewa Zone, and Amhara regional state from June 2022 to January 2023. Eight nationally released varieties of food and malt barley (Agegnehu-FB, Ibon-MB, Misrach-FB, Holker-MB, Local-FB, HB1964-MB, HB1307-FB, and Hagere-FB) were included in the experiment. The maximum grain yield (4.29 t/ha) was reported by HB1307-FB's food-feed barley, followed by Hagere-FB (4.03 t/ha) and Local-FB (2.27 t/ha). The highest and lowest means were found in the straw yields from HB1307-FB (4.92t/ha) and Ibon-MB (3.13t/ha), respectively. A higher CP content (4.02) was found for the Agegnehu-FB type, while HB1964- MB had a lower CP level. Moreover, it was found that the ADF content in HB1964-MB was lower (51.25%) and higher (53.88%) in Local-FB. In comparison to other food-feed barley cultivars, Agegnehu-FB exhibited the highest degradation (36.61) over the course of the 24-hour incubation period. Furthermore, Ibon-MB demonstrated the greatest degradation and local-FB the lowest after 96 hours of incubation. The component's potential degradability fraction (b) varied from 34.54 to 50.91%. HB1964-MB, Holker-MB, Agegnehu-FB, HB1307-FB, Misrach- FB, Local-FB, Hagere-FB, and Ibon-MB were ranked first, second, third, fourth, sixth, seventh, and eighth, respectively, according to the results of the participatory variety selection. In addition to producing more grain for human consumption, the Agegnehu-FB, HB1307-FB, Misrach-FB, Hagere-FB, and Ibon-MB varieties also had the potential to produce better grain, straws, and digestibility, which made them desirable possibilities for food-feed in the study area. Therefore, more research is required to assess and determine food-feed barley cultivars for different environments.